Temperatura e ácido bórico afetam a polinização de oliveiras nas condições de clima temperado - Dias, Camila Schwartz (2023)
The impacts of the environment in non-traditional olive growing regions (Olea europaea L.), on pollination stages and fruit setting are not yet fully understood. Thus, this study aimed to analyze the climatic conditions in Uruguay during the flowering season in different cultivars of olive trees in Uruguay and the action of temperature on pollination. It also aimed to study the action of low temperatures on pollination, as well as the identification of cultivars sensitive to low temperatures and the response of boron application on pollen germination. In the first experiment, the phenology of five olive cultivars (Arbequina, Arbosana, Manzanilla, Picual and Koroneiki) was observed, in vitro germination was tested and the pollen tube length of pollen grains was evaluated at temperatures of 0°, 10°, 15°, 20°, 25°, 30° and 40°C and the probability of occurrence of such temperatures. It was verified that the flowering period, in Uruguay, occurs from the 25th of September to the 16th of November. The Manzanilla cultivar is the earliest and Arbosana the latest. The temperature of 10°C inhibited germination and pollen grain length. Temperatures from 15 to 20°C are not effective for germination and pollen tube length and the optimum temperature occurs between 25° and 30°C. In Uruguay during flowering, there is a greater probability of occurrence of temperatures of 10 to 20°C. In the second experiment, the in vitro germination of pollen grains of Arbequina, Koroneiki, Gran Vitale, Galega and Panafiel cultivars was evaluated in order to identify the cultivars most sensitive to low temperatures. Adequate boron concentration (0, 100, 200, 300 and 400 mg L-1) for germination and pollen tube length of two olive tree cultivars at a temperature of 15°C was also evaluated. It was concluded that the temperature of 10°C inhibited the pollen grain germination of the Galega and Panafiel cultivars and reduced the germination of Gran Vitale. A few hours of exposure to a temperature of 10°C is enough to reduce germination and pollen grain length in sensitive cultivars. The concentration of 100mg L-1 is indicated to increase the parameters at low temperature and the cultivars Arbequina and Koroneiki are tolerant to low temperature, while Gran Vitale, Galega and Panafiel are sensitive.